Combining culture and microbead‐based immunoassay for the early and generic detection of bacteria in platelet concentrates. Issue 1 (15th November 2018) - Vossier, Ludivine; Valera, Lionel; Leon, Fanny; Roche, Stéphanie; Piquer, Dominique; Rubrecht, Laetitia; Favier, Christine; Cremer, Gaelle‐Anne; Pouzet, Agnès; Dagland, Typhaine; Rihet, Stéphane; Galea, Pascale; et al.
Abstract : BACKGROUND: Despite current preventive strategies, bacterial contamination of platelets is the highest residual infectious risk in transfusion. Bacteria can grow from an initial concentration of 0.03–0.3 colony‐forming units (CFUs)/mL up to 10 8 to 10 9 CFUs/mL over the product shelf life. The aim of this study was to develop a cost‐effective approach for an early, rapid, sensitive, and generic detection of bacteria in platelet concentrates. STUDY DESIGN AND METHODS: A large panel of bacteria involved in transfusion reactions, including clinical isolates and reference strains, was established. Sampling was performed 24 hours after platelet spiking. After an optimized culture step for increasing bacterial growth, a microbead‐based immunoassay allowed the generic detection of bacteria. Antibody production and immunoassay development took place exclusively with bacteria spiked in fresh platelet concentrates to improve the specificity of the test. RESULTS: Antibodies for the generic detection of either gram‐negative or gram‐positive bacteria were selected for the microbead‐based immunoassay. Our approach, combining the improved culture step with the immunoassay, allowed sensitive detection of 1 to 10 CFUs/mL for gram‐negative and 1 to 10 2 CFUs/mL for gram‐positive species. CONCLUSION: In this study, a new approach combining bacterial culture with immunoassay was developed for the generic and sensitive detection of bacteria in platelet concentrates. This efficient and easily automatable approach allows tested platelets to be used on Day 2 after collection and could represent an alternative strategy for reducing the risk of transfusion‐transmitted bacterial infections. This strategy could be adapted for the detection of bacteria in other cellular products.